Building Homestay User Loyalty with Operational Risk Management Mediated by Satisfaction - Dwiyono Rudi Susanto; Sugiarto Sugiarto; Amin Kiswantoro; Tonny Hendratono; Sony Heru Priyanto; Fongnawati Budhijono; Nur Rohman (Jurnal Manajemen, 2025)
Tourists' increasing interest in homestays requires operational risk management for the homestays' sustainability. This study confirms the reliability of homestay operational risk management indicators, tested in Wukirsari tourist village, Yogyakarta, and Dieng tourist village, Central Java. The research respondents were homestay users with experience staying in homestays in both locations. Multi-stage sampling techniques collected data. This mixed-method study used a sequential explanatory design. The structural Equation Model analysed the relationship between Operational Risk Management and Loyalty mediating by satisfaction. Empirical data found that homestay user satisfaction was significantly positively influenced by the performance of operational risk management implemented in homestays in two research locations. It was discovered that satisfaction among homestay users significantly positively influenced their loyalty. Success in satisfying homestay users increases the intention of homestay users to revisit and recommend the homestays they have used to others.